Youth exclusion and empowerment in the contemporary global order : contexts of economy, education and governance - Akanle, Olayinka (Emerald Publishing Limited, 2022)
The existential exclusion of youths from the mainframe of the current global order is an increasingly pressing issue. Research to date has proven youths struggle to survive and be relevant within current systemic and institutional arrangements, resulting in a major existential and generational problem. One of two volumes filling a gap in the literature in understanding and responding to this grand challenge, this edited collection focuses particularly on contexts of economic, educational and governance concerns that confront youths, the complex consequences of these issues, their experience of exclusion, and sustainable pathways forward. Addressing youth issues from around the world, Youth Exclusion and Empowerment in the Contemporary Global Order engages with practical, pragmatic, intellectual and policy perspectives. Delving into the lived experiences of young people in many countries, the chapters bring together a rich collection of research from diverse methodologies. Revealing how young people appear trapped, strategically excluded, and helplessly frustrated by the supposedly supportive institutional frameworks of society, the authors tackle this question: how can young people become empowered and socially active in this context? The original materials, literature and data collated across both volumes of Youth Exclusion and Empowerment in the Contemporary Global Order, addressing policy and practice issues for youth, present a cutting edge and innovative major contribution to the field of global youth studies.
Keywords: Youth -- Economic conditions -- 21st century.; Youth -- Social conditions -- 21st century.; Youth -- Political activity.; Youth -- Cross-cultural studies.; Social Science -- Sociology -- General.; Sociology.; elektronické knihy; electronic books